2009
DOI: 10.1158/0008-5472.can-08-3806
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Muc1-Regulated β-Catenin Stability Results in Aberrant Expansion of CD11b+Gr1+ Myeloid-Derived Suppressor Cells from the Bone Marrow

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of myeloid cells that inhibit T-cell activity and contribute to the immune suppression characteristic of most tumors. We discovered that bone marrow (BM) progenitor cells from the Muc1 knockout (KO) mice differentiated into CD11b + Gr1 + MDSCs in vitro under granulocyte macrophage colony-stimulating factor and interleukin-4 signaling. MUC1 is a tumor-associated mucin and its cytoplasmic tail (MUC1-CT) can regulate B-catenin to promote onco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Our finding that the negative regulation of MDSCs by CUL4B is mediated by b-catenin is consistent with two recent reports of b-catenin being a negative regulator of MDSCs (17,18). We showed that pharmacologic inhibition of GSK3b drastically reduced the growth of tumor grafts in Cul4b CKO mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that the negative regulation of MDSCs by CUL4B is mediated by b-catenin is consistent with two recent reports of b-catenin being a negative regulator of MDSCs (17,18). We showed that pharmacologic inhibition of GSK3b drastically reduced the growth of tumor grafts in Cul4b CKO mice.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies indicated that a tight regulation of Wnt signaling is required for normal hematopoiesis and lymphopoiesis (12)(13)(14)(15). b-Catenin was recently shown to negatively regulate the functions of immunosuppressive cells, including regulatory T cell (Treg) and MDSCs (16)(17)(18). However, how Wnt signaling is regulated in those immunosuppressive cells remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of both EP2 and EP4 heterotrimeric guanine nucleotide-binding protein (G protein)-coupled receptors could liberate G protein bg subunits and activate the phosphoinositide 3-kinase pathway, which is likely to be a vital signaling event in generation of MDSCs in BM. 38 Moreover, the immunosuppressive function of PMN-MDSCs is dramatically reduced in aspirintreated/COX-1-deficient mice and in patients with AIA, which is also correlated with arginase activity in PMN-MDSCs. Moreover, COX-1 expression was downregulated in nasal/bronchial epithelial cells and fibroblasts from patients with AIA.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of MDSCs to recipient mice was performed 4 days after inoculation with 4T1 cells, and then given every 7 days thereafter for 3 weeks. Tumors at the site of injection were measured using an electronic calipers and tumor diameters were calculated as the square root of the length × width of the tumor as previously described [16,54]. Mice were sacrificed for endpoint analyses when the diameter of the tumor reached > 20 mm.…”
Section: Immune Function Assaymentioning
confidence: 99%